Detection and Culture of Bartonella quintana, Serratia marcescens, and Acinetobacter spp. from Decontaminated Human Body Lice - La Scola, Bernard (American Society for Microbiology, 2001)
As part of a survey for trench fever among homeless people in Marseilles, France, we attempted isolation of Bartonella quintana from body lice. A decontamination protocol of immersion in 70% ethanol with 0.2% iodine was devised and was tested with a laboratory colony of body lice. Lice which had been experimentally contaminated with either Escherichia coli, Staphylococcus epidermidis, or Acinetobacter spp. were successfully decontaminated, and this process did not prevent the culture of B. quintana from these lice. One hundred sixty-one lice obtained from homeless patients were studied by the protocol. B. quintana was isolated on axenic medium from 15 of 161 body lice and was detected in 41 of 161 lice by PCR. Acinetobacter spp. and Serratia marcescens were also isolated from body lice. The sensitivities of PCR and culture of B. quintana were 98 and 36%, respectively. These procedures may be useful for epidemiologic studies of trench fever and for the recovery of strains for characterization and comparison.